The Legitimacy of Conjugal Visit Facilities: a Legal Analysis under National and International Law - Wiwin Wiwin (Jurnal Litigasi Amsir, 2025)
This study examines national and international legal frameworks concerning the provision of conjugal visit facilities (commonly referred to as “bilik asmara”) for inmates in Indonesia, which currently lacks explicit legal regulation. The core issue lies in a legal vacuum (rechtsvacuum) that results in uncertainty regarding the legality of such facilities and weak protection of prisoners’ fundamental rights, particularly the right to family life and sexual rights. The objective of this research is to analyze the legitimacy of conjugal visit facilities from the perspectives of both national and international law. This study adopts a normative legal research method, utilizing statutory and analytical approaches. The findings indicate that Indonesia’s national legal system provides implicit legitimacy for the provision of conjugal visits, as reflected in Article 28B(1) of the 1945 Constitution, Law No. 1 of 1974 on Marriage, Law No. 22 of 2022 on Corrections, and Law No. 39 of 1999 on Human Rights. These legal instruments affirm the state's responsibility to fulfill the sexual rights of inmates within the institution of marriage. Additionally, international legal legitimacy is implicitly found in Article 10(1) of the International Covenant on Civil and Political Rights (ICCPR), ratified by Law No. 12 of 2005, and Article 10 of the Universal Declaration of Human Rights, both of which guarantee humane treatment of prisoners. The provision of conjugal visit facilities constitutes a fulfillment of inmates’ constitutional rights and the state’s international obligations in protecting human rights. This study underscores the importance of harmonizing international norms with national legislation to realize a humane and just correctional system.